PENGARUH TINGKAT KONSENTRASI EFFECTIVE MIKROORGANISM 4 (EM 4) TERHADAP KEPADATAN LALAT PETERNAK SAPI (STUDI DI TEMPAT DESA SIDOMUKTI KECAMATAN BANDUNGAN KABUPATEN SEMARANG) - Tariyadi Tariyadi; Retno Hestiningsih; Martini Martini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Flies are insects and act as mechanical vectors for various diseases. These insects have always coexisted with humans. Preliminary survey results obtained 10.8 birds / flygrill categorized as high density. One effort to reduce the density of flies using four effective microorganism (EM 4). The research objective was to determine the effect of four concentrations of effective microorganism (EM 4) to the density of flies. The study design used is True Experiment with models pretest posttest with control group. This research was conducted in the village of cattle breeders Sidomukti Subdistric Bandungan District of Semarang. The real test with a concentration of 0.328%: 0.656%: 1.312%: 2.624%, and 5.246%. With the control and treatment carried out 5 and 5 repetitions needed 30 cowshed. From statistical test their mean level of concentration of the density of flies before and after use of effective microorganism 4 obtained sequentially is 43.70%: 52.30: 74.11%: 79.58%: 85.24% -1.73% while the average control. Furthermore, to examine differences in concentration and control test Kruskal Wellis test with significance level of 0.05 (p = 0.05) with a 95% confidence level (α) 0.05 p value (probalibilitas) 0.000 <0.05 shows there differences in the level of concentration of the density of flies. To determine the effective concentration level, then used mann whetney test with p <0.05, the analysis of the respective mean concentrations of p <0.05 showed no significant difference. As for suggestions for effective concentration is 5.248% with a mean of 85.24% decrease.